The choice of treatment and the motivations behind it impact clinical outcomes among patients with adequate control of their rheumatic disease: A real-life study. - Irazú Contreras-Yáñez; Guillermo A Guaracha-Basáñez; Diana Padilla-Ortiz; Laura L Franco-Mejía; Laura V Vargas-Sánchez; Julia G Jiménez-Decle; Virginia Pascual-Ramos (PLoS ONE)
Introduction Many factors influence how doctors make treatment decisions. The study compares the outcomes of patients with rheumatic diseases and adequate control (AC) whose treating rheumatologists prescribed their first choice of treatment (FCHO) versus the second choice (SCHO) and the motivations behind them. It also investigates the motivations associated with FCHO. Patients and methods The study was conducted at an outpatient clinic from February 2023 to February 2024. Patients with an RMD diagnosis were identified using systematic sampling (P-1). After their consultation, their rheumatologists detailed their treatment choice (FCHO vs. SCHO), the motivations behind it, and the outcomes. In a subsample of patients from P-1 and AC (SubP-1), treating rheumatologists repeated the assessment of outcomes at the next scheduled consultation. Descriptive statistics and multivariate regression analysis were used. Results There were 703 patients enrolled (P-1), 543 (77.2%) had AC, and 292 (Subp-1) underwent a follow-up evaluation. In P-1 and subP-1, FCHO was prescribed to 644 (91.5%) and 269 (92.1%) patients. Motivations related to evidence-based medicine and personal experience were more frequently referred to in FCHO. Concerns related to current or future drug shortages and a history of adverse events/intolerance were more frequent in SCHO. In SubP-1, a higher proportion of patients remained in AC and experienced remission/ improved disease activity with FCHO. Patients who received FCHO experienced a greater risk for favorable outcomes. The following motivations were associated with FCHO: "It aligns with guidelines"; "solid scientific evidence supporting the treatment effectiveness"; "I am concerned that the shortage of the drug may hinder the continuation of the treatment" and "history of adverse events or intolerance". Conclusions Patients with AC of their underlying RMD, whose rheumatologists prescribed their FCHO, had better outcomes than those who were prescribed SCHO. Evidence-based motivations, rheumatologists´ concern of medication shortage, and patient-related motivations were associated with FCHO.